Use of sodium-glucose cotransporter-2 inhibitors and urinary tract infections in type 2 diabetes patients: a systematic review - Figueiredo,Izabela Rodrigues (2019)
SUMMARY Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are drugs that act by maintaining glycosuria. Recent studies have shown promising effects of these in the treatment of type 2 diabetes mellitus (DM2). However, there may be an increased risk of developing urinary tract infections (UTIs) in patients treated with these. Our study aims to analyze the association between the risk of UTI in patients treated with SGLT2i. A systematic review of the literature was carried out by randomized clinical trials, totalizing at the end of the selection 23 articles that were statistically evaluated. The incidence of UTI was generally demonstrated in articles and in different subgroups: patients on SGLT2i monotherapy or on combination therapy; according to specific comorbidities of each sample or according to the drug used. They noticed an increase in the chance of UTI in the SGLT2i groups compared to the control groups on placebo or other oral antidiabetic agents. This increased chance was found predominantly with the use of Dapagliflozin, Canagliflozin, and Tofogliflozin, regardless of the dosing. Lastly, stands out that the dimension of UTI chances for DM2 patients who use SGLT2i remains to be more strictly determined.